EFEKTIVITAS SEDIAAN OBAT KUMUR EKSTRAK ETANOL DAUN RAMBUTAN SEBAGAI ANTIBAKTERI Streptococcus mutans PENYEBAB KARIES GIGI - Fatayati, Imma; Qatrunada, Putri Norfa; Sungkawa, Hendra Budi; Supriyanto, Supriyanto (SINERGI : Jurnal Riset Ilmiah, 2025)
Mouthwash is an antiseptic liquid known to eliminate bad breath. Rambutan leaves contain antibacterial compounds such as flavonoids, alkaloids, saponins, and tannins, which can be used as active ingredients. The purpose of this study was to determine the effect of a mouthwash containing ethanolic extract of rambutan leaves at concentrations of 5%, 10%, and 15% on inhibiting the growth of Streptococcus mutans. The sampling technique used was purposive sampling, using a bacterial culture diffusion method using MHA media for bacterial testing. The were three mouthwash treatments: 5%, 10%, and 15% concentrations, with 10 repetitions, resulting in a total of 30 replication. The average inhibition zone at a concentration of 5% was 9.4 mm (moderate), the concentration of 10% was 11 mm (strong), and the concentration of 15% was 11.4 mm (strong). Based on the result of a simple linear regression statistical test, a significance value (p=0.000) < 0.05 was obtained, indicating that the mouthwash made from rambutan leaf ethanol extract affects the inhibition of Streptococcus mutans bacteria. This study concludes that the mouthwash made from rambutan leaf ethanol extract is effective in inhibiting Streptococcus mutans bacteria, with the highest inhibition zone at a concentration of 15%.